ANALISIS TATA RUANG KANTOR DI BKPSDM KOTA SURABAYA (Studi Pada Bidang Pengelolaan Kinerja Pegawai) - Rizaldy Hafizh Imawan; Dian Arlupi Utami (Jurnal Inovasi Administrasi Negara Terapan (Inovant), 2023)
Office arrangement involves the arrangement of room layouts and the arrangement of office furniture according to the available office space. A well-organized and effective office layout will influence the work efficiency of the employees. The purpose of this research is to describe the office spatial arrangement at the Personnel and Human Resources Development Agency of Surabaya City in the Field of Employee Performance Management. The research type used is descriptive research with a qualitative approach. The techniques used in data collection for this research are observation, interviews, and documentation using purposive sampling technique. The data analysis technique consists of 4 stages: data collection, data reduction, data presentation, and drawing conclusions or verification. The research focuses on the office spatial arrangement and the physical environmental factors of the office. The research results indicate that the combined office room layout is still ineffective, both for the staff employees' office space and the head of department's office space. Additionally, the number of staff employees does not match the available office space. Regarding the physical environmental factors of the office, lighting and color indicators are well-implemented, but air and sound indicators have not been well-implemented. Recommendations that the researcher can provide for the institution regarding the office spatial arrangement include the need for rules limiting the entry and exit of guests from other institutions into the office space to avoid guest accumulation/queues inside the office space. For the leadership room, it is suggested to install sliding doors between the leader's work desk and the guest reception desk. As for the office's physical environment, for the sound indicator, it is suggested to install sound dampers if possible on the northern window side facing the school, though this might result in the closure of windows through which air enters. For the air indicator, it is recommended to add more air conditioning units to the office space.   Keywords: Office Spatial Arrangement, Physical Work Environment, Personnel and Human Resources Development Agency (BKPSDM) of Surabaya City.